(untitled) - Willard, Nancy; Moser, Barry (Harcourt Brace Jovanovich, 1992)
A retelling, set in the early 1900's in New York City, of the traditional tale in which a kind and beautiful young woman, through her great capacity to love, releases a handsome young man from the spell which has made him into an ugly beast.
Kirkus
Booklist
Horn Book
Sch Libr Jnl
Keywords: Fairy tales; Folklore; France